Trombocitosis y su relación con anemia ferropénica en niños menores de 2 años del cantón Alausí, Chimborazo. - Cerda Maldonado, Kaily Cristina (2025)
Iron deficiency anemia is a hematological disease caused by iron deficiency in the body that can be due to several factors, with the nutritional shortage of iron the most common cause; therefore, infants, children, pregnant women, and women of childbearing age are the most vulnerable population considering that their physiological needs require more iron in their body. This research aimed to determine the parameters of hemoglobin, serum iron, ferritin, and platelets to assess thrombocytosis and its relationship with iron deficiency anemia. The applied study is a descriptive, non-experimental, cross-sectional field whose population consisted of 200 children under 2 years of age in the Alausí canton. The researcher selected 58 children for the study by applying exclusion and inclusion criteria. Ferritin and hemoglobin levels were the main parameters for diagnosing iron deficiency anemia. In addition, it was possible to identify the presence of platelet alterations characterized by elevated platelet count. According to the data analyzed, it was possible to determine that of the 12 children diagnosed with iron deficiency anemia, 7 of them presented thrombocytosis, representing 58% prevalence in this pathology; however, applying the chi-square statistical tool, the null hypothesis was accepted, that is to say, that there is no relationship between thrombocytosis and iron deficiency anemia.